2022
DOI: 10.1002/1348-9585.12373
|View full text |Cite
|
Sign up to set email alerts
|

Corporate health culture promotes infection control measures against COVID-19 in the workplace

Abstract: Objectives The present study examined the relationship between health culture evaluated by the Health and Productivity Survey Sheets and the implementation status of infection control measures against COVID‐19 in the workplace. Methods This was a cross‐sectional study using the corporate data (2518 companies) collected for the purpose of selecting the excellent company of health and productivity management by the Japanese government. The explanatory variable was the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…A subset of 29 997 of these respondents met the inclusion criteria. The study protocol has previously been reported in detail 25 …”
Section: Methodsmentioning
confidence: 99%
“…A subset of 29 997 of these respondents met the inclusion criteria. The study protocol has previously been reported in detail 25 …”
Section: Methodsmentioning
confidence: 99%